Ticks, fleas and rodent-hosts analyzed for the presence of Borrelia miyamotoi in Slovakia: the first record of Borrelia miyamotoi in a Haemaphysalis inermis tick - Heglasová, Ivana; Rudenko, Natalie; Golovchenko, Maryna; Zubriková, Dana; Miklisová, Dana; Stanko, Michal (Ticks and tick-borne diseases, 2020)
In Slovakia, little knowledge is available on the occurrence, hosts and vectors of Borrelia miyamotoi of the relapsing fever group. In the current study, 2160 questing and rodent-attached ticks of six species (Ixodes ricinus, Ixodes trianguliceps, Dermacentor marginatus, Dermacentor reticulatus, Haemaphysalis concinna and Haemaphysalis inermis), 279 fleas belonging to 9 species (Ctenophthalmus agyrtes, Ctenophthalmus solutus, Ctenophthalmus assimilis, Megabothris turbidus, Amalareus penicilliger, Hystrichopsylla orientalis, Ctenophthalmus uncinatus, Doratopsylla dasycnema and Nosopsyllus fasciatus) and skin biopsies from 245 small mammals belonging to eight species (Apodemus agrarius, Apodemus flavicollis, Apodemus uralensis, Myodes glareolus, Crocidura leucodon, Micromys minutus, Microtus arvalis, Microtus subterraneus) were screened for the presence of B. miyamotoi DNA. The overall prevalence of B. miyamotoi found in questing and rodent-attached ticks was 1.8% (23 positive/1260 examined) and 3.4% (31 positive/900 examined), respectively. Borrelia miyamotoi was detected in questing I. ricinus, rodent-attached I. ricinus and H. inermis ticks, and in one male of the common vole (M. arvalis) in different habitats (mainly rural) in eastern Slovakia. However, B. miyamotoi was not found in any of the tested fleas. Our findings indicate that rural habitats with different species of tick vectors and hosts are appropriate for the occurrence of B. miyamotoi.
Keywords: Environment; Animals; Prevalence; Rodentia; Borrelia Infections; Borrelia miyamotoi; Slovakia; Host-Parasite Interactions; Siphonaptera; interakce hostitele a parazita; Ixodidae; prevalence; Ticks; Fleas; infekce bakteriemi rodu Borrelia; životní prostředí; hlodavci; Slovenská republika; zvířata; Rodents; Borrelia